THE INFLUENCE OF SHORT MESSAGE SERVICE TEXTING ON STUDENTS’ WRITING DESCRIPTIVE PARAGRAPH ACHIEVEMENT - Asti Veto Mortini (Universitas PGRI Palembang, 2017)
The objective of this research was to find out was any significant influence between the third semester students of University of PGRI Palembang majoring English Education who are taught using Short Message Service (SMS) texting in learning writing descriptive paragraph and those who are not. Quasi experimental method was used in this research. One group experimental and one control groups were as samples. Data were collected through written tests; pretest and posttest and analyzed them using independent sample test. The result showed t-obtained was greater (2.855) than t-table (1.990) at the significance level p<0.05 in two tailed testing with df=75. It means that there was a significant influence between the third semester students of University of PGRI Palembang majoring English Education who are taught using Short Message Service (SMS) texting in learning writing descriptive paragraph and those who are not. Keywords: Short Message Service Texting, writing, descriptive paragraph.